Influence of incubation time and action of fluid flow on SPEV cell adhesion strength to a glass substrate - Todrin, A.F.; Timofeyeva, O.V.; Petrenko, T. P. (Journal of Adhesion Science and Technology, 2018)
The results of study of SPEV cell adhesion to the glass substrate that were obtained with a radial-flow chamber shown that in some cases the cells which were incubated on the substrate for a longer time were more strongly attached to it, and under certain conditions such cells detached easier than cells with a shorter incubation time. For example, when the channel height was decreased more of cells were detached from substrate with increasing incubation time. Besides an increase of flow action time on the cells increased an amount of detached cells, and an increase of initial shear stress resulted in decrease an amount of cells which detached from the surface regardless of incubation time. During each experiment more spread cells detached from the substrate earlier than the more spherical one. When both the flow rate and channel height were reduced in the radial-flow chamber, but the initial shear stress was the same as before the changes of these parameters, then the critical radius, the critical shear stress and the time of reach these critical values sharply decreased. In addition, in this case, the area of the projection of cells remaining on the substrate also decreased.
Keywords: strength; incubation time; flow action time; initial shear stress; critical radius; critical shear stress; cell projection area